A Report of Guillain–Barré Syndrome With Myalgia and Mild Weakness - AMINZADEH*, Vahid; HASSANZADEH RAD, Afagh (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Aminzadeh V, Hassanzadeh Rad A. A Report of Guillain–Barré Syndrome With Myalgiaand Mild Weakness. Iran J Child Neurol. 2014 Spring; 8(2):70-72. We report a rare case that revealed severe myalgia as the chief complaint that is not mentioned in the list of frequent symptoms of Guillain Barré. Guillain-Barré syndrome (GBS) is an acute inflammatory demyelinating polyneuropathy (AIDP).Required features for diagnosis of GBS are progressive motor weakness of more than one limb and areflexia. We report an 11-yearold boy who was referred to the emergency department with complaints of generalized body pain and gate problem. It seems that if myalgias are the chief complaint and weakness is mentioned as a less important symptom, clinicians should consider GBS after ruling out other reasons for myalgia especially inflammatory myositis. References 1. Landaverde JM, Danovaro-Holliday MC, Trumbo SP, Pacis-Tirso CL, Ruiz-Matus C. Guillain-Barré syndrome in children aged <15 years in Latin America and the Caribbean: baseline rates in the context of the influenza A (H1N1) pandemic. J Infect Dis 2010 Mar;201(5):746-50. 2. Edward J. Filipponea, D Mitul Kanzariaa Rodney Bellb Eric Newmana, D John L. Farber. Secondary Membranous Nephropathy Associated with Guillain-Barré Syndrome. Case Rep Nephrol Urol 2013;3:34–39. 3. Kuwabara S. Guillain-Barré syndrome: epidemiology, pathophysiology and management. Drugs 2004;64(6):597-610. 4. Hughes RAC, Swan AV, Raphael JC, Annane D, van Koningsveld R, van Doorn PA. Immunotherapy for Guillain-Barré syndrome: a systematic review. Brain 2007;130:2245-2257. 5. Dy M, Leshner RL, Crawford JR An Unusual Case of Recurrent Guillain-Barre Syndrome of a Different Subtype Five Years after Initial Diagnosis.Case Rep N eurol Med 2013; 2013: 356157. 6. McLean S, Sheng F, Oon SF. Childhood Guillain-Barre Syndrome: Comparing Intravenous immunoglobulin Treatment with Supportive Care.Trinity Student Medical Journal. 2005; 6:60–7. 7. Swaimann K. Ashwal S. Ferriero D. Pediatric neurology: principles and practice. 4th ed. Philadelphia: Mosby-Elsevier 2006.p 1920. 8. Sejvar JJ, Kohl KS, Gidudu J, et al. Guillain-Barré syndrome and Fisher syndrome: case definitions and guidelines for collection, analysis, and presentation of immunization safety data. Vaccine 2011;29:599-612. 9. Hicks CW, Kay B, Worley SE, Moodley M. A clinical picture of Guillain-Barré syndrome in children in the United States. J Child Neurol 2010 Dec;25(12):1504-10. 10. Borade A, Lad S, Ansari N, Dhongade R. Guillain-Barré syndrome in child with prolongintubation. Indian J Med Sci 2010 Jul;64(7):325-8. 11. Roodbol J, de Wit MC, Walgaard C, de Hoog M, Catsman-Berrevoets CE, Jacobs BC. Recognizing Guillain-Barré syndrome in preschool children. Neurology 2011 Mar 1; 76(9):807-10.